(untitled) (University Heart Journal, 2011)
Cardiac syndrome X is a multifactorial disorder. A triad of angina pectoris, positive exercise tolerance test (ETT) and angiographically normal epicardial coronary arteries, is called Cardiac syndrome X. Though the normal epicardial coronary arteries, patients present with debilitating chest pain which increases morbidity and poor quality of life. The particular cause of Cardiac syndrome X is still unknown. Many large trails are on going to detect exact pathogenesis of this condition. A multiple treatment regimens may reduce the morbidity and improve the quality of life of these patients. Key words: Angina pectoris; exercise tolerance test. DOI: 10.3329/uhj.v6i1.7188 University Heart Journal Vol.6(1) 2010 pp.32-34